AI for games : artificial intelligence - Millington, Ian, ....- (Boca Raton (Fla.) : CRC Press : AOCS Press, 2019)
AI is an integral part of every video game. This book helps propfessionals keep up with the constantly evolving technological advances in the fast growing game industry and equips students with up-to-date infortmation they need to jumpstart their careers. This revised and updated Third Edition includes new techniques, algorithms, data structures and representations needed to create powerful AI in games. The companion website includes downloadable and executable source code that will be regularly updated by the author. Key Features •A comprehensive professional tutorial and reference to implement ture AI in games •Includes new exercises so readers can test their comprhension and understanding of the concepts and preactices presented •Revised and updated to cover new techniques and advances in AI •Walks the reader throuigh the entire game AI development process •New and improved companion website with easily downloaded and executable source code
Keywords: Artificiële intelligentie